1986
DOI: 10.1007/bf02555368
|View full text |Cite
|
Sign up to set email alerts
|

A study of optimal length of flexible fiberoptic sigmoidoscopes for initial endoscopic training

Abstract: Eighteen trainees with no prior fiberoptic endoscopic experience performed a total of 305 fiberoptic sigmoidoscopies using a colonoscope. Basic training, consisting of reading materials, lecture instructions, practice on a colon model, and observation of procedures, was completed prior to beginning patient examinations. Additional instruction was given between examinations. The performance of these examinations was an individual effort on the part of the trainee without verbal or mechanical assistance from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Few adenomas were detected in the right side of the colon, but 8 patients had screen-detected cancer. Flexible sigmoidoscopy plus double-contrast barium enema (DCBE) instead of full colonoscopy would miss some of the neoplasms in the right side and probably also in the descending colon, which may not be reached in more than 20% of the persons having flexible sigmoidoscopy [16]. Rigid proctoscopy plus DCBE would be even less sensitive because of the low accuracy for neop!asia by DCBE in the sigmoid colon [17].…”
Section: Discussionmentioning
confidence: 99%
“…Few adenomas were detected in the right side of the colon, but 8 patients had screen-detected cancer. Flexible sigmoidoscopy plus double-contrast barium enema (DCBE) instead of full colonoscopy would miss some of the neoplasms in the right side and probably also in the descending colon, which may not be reached in more than 20% of the persons having flexible sigmoidoscopy [16]. Rigid proctoscopy plus DCBE would be even less sensitive because of the low accuracy for neop!asia by DCBE in the sigmoid colon [17].…”
Section: Discussionmentioning
confidence: 99%
“…16 The results of the Painter study were similar to those of Lehman et al who used endoscopically placed clips before barium enema to identify the proximal depth of insertion at FS. 8,17 They found that the sigmoidoscope had not passed into the descending colon in 48% of patients. Jensen et al used plain abdominal X ray to determine depth of insertion of the 60 cm flexible sigmoidoscope and found that they failed to enter the descending colon in 34% of patients.…”
Section: Diagnostic Choices and Their Inherent Errorsmentioning
confidence: 98%